Management strategies adopted by companies in the road construction subsector in response to the COVID-19 pandemic situation (Revista Científica Compendium, 2024)
The purpose of this study was to analyze the managerial strategies adopted by companies in the road construction subsector in response to the COVID-19 pandemic situation in Barquisimeto, the State of Lara. From a methodological perspective, it is a descriptive field research, in which is considered as a unit of analysis four (4) companies registered in the RNC and that executed road works projects with public institutions. The information was collected through a guided interview and a Likert scale questionnaire, allowing the application of tools such as Porter's Diamond and descriptive statistics to evaluate the strategic performance of these organizations in the face of the effects of the COVID-19 pandemic. The conclusions indicate that these companies have a weak vision of the future due to the conditions of uncertainty, focusing their objectives on resolving the conditions that frame the environment in order to fulfill the execution of the project in the most effective way possible.